Предмет: Математика,
автор: NarutaUchiha
Упростите выражение
1,2m+3,9m-2,1m+13
m=0,9
Ответы
Автор ответа:
3
Пошаговое объяснение:
= 3m+13= 3*0,9+13= 15,7
NarutaUchiha:
Спасибо
Автор ответа:
1
Ответ: 15.7
Пошаговое объяснение:
1.2m+3.9m-2.1m+13 = 3m+13
(m=0.9)
3m+13 = (3*0.9) + 13 = 2.7+13 = 15.7
Похожие вопросы
Предмет: Русский язык,
автор: denis03112002
Предмет: Английский язык,
автор: Аноним
Предмет: Английский язык,
автор: Светлана2852
Предмет: Алгебра,
автор: llvoronall
Предмет: Українська мова,
автор: scorpion66